THE EFFECT OF MBKM ON STUDENTS' KNOWLEDGE SHARING INTENTION: AN EMPIRICAL STUDY BASED ON THEORY OF PLANNED BEHAVIOR - Akbarini, Nur Rahmi (JURNAL EDUSCIENCE, 2025)
Purpose-In an increasingly complex era of globalization, the ability to share knowledge is becoming increasingly important. The main objective of this study is to investigate the effect of MBKM on students' knowledge-sharing behavior using the Theory of Planned Behavior (TPB) as a theoretical framework.Methodology: This study used a quantitative approach with PLS-SEM (Partial Least Squares-Structural Equation Modeling) statistical analysis method to examine the relationship between factors in TPB and students' knowledge-sharing intention after participating in MBKM. Data collection was conducted through surveys and using valid instruments that had been previously prepared. The population of this study was all students majoring in teaching who had participated in the MBKM program at Sebelas Maret University. The sampling technique of this study used a convenience sampling technique; at the end of the study, it obtained answers from respondents of students majoring in teacher education who had attended the MBKM program 262 students.Findings- The results showed that Attitude has a significant and positive effect on knowledge-sharing intention, perceived behavioral control has a significant and positive effect on knowledge-sharing intention, and the subjective norm has a significant and positive effect on knowledge-sharing intention. The results of this study are expected to provide deeper insight into the factors that influence the knowledge-sharing intentions of students majoring in teaching.Significance-The implications of the findings of this study are expected to contribute to the development of students' ability to share knowledge.Keywords: Knowledge Sharing Intention, Theory of Planned Behavior, MBKM